2013
DOI: 10.3389/fneur.2013.00016
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI in the Investigation of Blast-Related Traumatic Brain Injury

Abstract: This review focuses on the application of functional magnetic resonance imaging (fMRI) to the investigation of blast-related traumatic brain injury (bTBI). Relatively little is known about the exact mechanisms of neurophysiological injury and pathological and functional sequelae of bTBI. Furthermore, in mild bTBI, standard anatomical imaging techniques (MRI and computed tomography) generally fail to show focal lesions and most of the symptoms present as subjective clinical functional deficits. Therefore, an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 241 publications
(297 reference statements)
2
15
0
Order By: Relevance
“…A review by Graner and colleagues summarizing the applications of functional magnetic resonance imaging (MRI) suggested that bTBI survivors may experience symptoms related to stress and emotional disturbance related to underlying brain change (e.g., activation of the amygdala). 273 Clinically, there is a challenge in separating out these problems from more-severe psychological consequences, such as PTSD and major depressive disorder, both of which are common in military personnel. 274,275 In the context of animal models, bTBI led to prolonged psychological dysfunction for months, including enhanced contextual fear conditioning.…”
Section: Stress-related Outcomesmentioning
confidence: 99%
“…A review by Graner and colleagues summarizing the applications of functional magnetic resonance imaging (MRI) suggested that bTBI survivors may experience symptoms related to stress and emotional disturbance related to underlying brain change (e.g., activation of the amygdala). 273 Clinically, there is a challenge in separating out these problems from more-severe psychological consequences, such as PTSD and major depressive disorder, both of which are common in military personnel. 274,275 In the context of animal models, bTBI led to prolonged psychological dysfunction for months, including enhanced contextual fear conditioning.…”
Section: Stress-related Outcomesmentioning
confidence: 99%
“…Several prior reviews have been written on TBI and mTBI in the civilian and Veteran fields extending from the peri-2009 period and before [20][21][22][23][24][25][26][27][28][29][30]. It is recommended that these prior sources complement this work.…”
Section: Prior Reviewsmentioning
confidence: 99%
“…) – a system that may be affected by blast mTBI (Graner et al. ). The precuneus, per se, has shown both reduction in resting cerebral blood flow (Kim et al.…”
Section: Functional Connectivity Of Visual Pathway Nodesmentioning
confidence: 99%
“…Precuneus has been suggested to be a "core node" or "hub" of the default-mode network (Fransson and Marrelec 2008), and it exhibits resting state FC with visual cortex (Margulies et al 2009). Given the proposed role of precuneus in directing attention (Cavanna and Trimble 2006), and its strong interconnections with prefrontal cortex (Cavanna and Trimble 2006), this visual cortex/ precuneus FC is likely part of a system involved in the regulation of visual attention (Lauritzen et al 2009)a system that may be affected by blast mTBI (Graner et al 2013). The precuneus, per se, has shown both reduction in resting cerebral blood flow (Kim et al 2010) and decreased regional volume (Zhou et al 2013) as a function of severity of TBI, conditions that could contribute to current findings of reduced V1/precuneus FC with blast mTBI severity.…”
Section: Functional Connectivity Of Visual Pathway Nodesmentioning
confidence: 99%